A Cross-Cultural Reference of the 17th Century Bugis Community in the 22nd King of Bone's Diary (Study of Historical Literature) - Kasma F. Amin (Jurnal Multidisiplin Madani, 2023)
This study aims to explore 'historical literary archives related to local culture' of Indonesia so that certain knowledge about cross-cultural activities, attitude structures, and cultural references that have influenced historical culture can be used as cultural references that are valued as the values of today's society. One of the old texts that contains various cross-cultural events in the past in South Sulawesi is the 22nd Diary of the King of Bone, namely La Tommassongek To appawelling Matinroe in Mallimongan. The works which are classified as historical literature contain experiences, expressions, and cross-cultural understandings of their time. The object of research is the Diary of the King of Bone in the 17th Century AD. The research method used is descriptive qualitative with a cross-cultural psychological approach. The results of the research show that cross-cultural representation in the form of strong individualism-collective values. This is based on four aspects of indicators, namely: a) Harmony in socializing is represented in the relationship between the King of Bone and other powerful kings, as well as foreigners such as the Dutch (Tomarajae); b) Cooperate in social groups that are represented in the culture of building houses, irrigation facilities, places of worship, and cultural celebrations, and; c) Self-control in relation to social groups is represented in an attitude of mutual assistance and protection in defending oneself, family and country; d) Give recognition or appreciation that is represented by mappacella and massolo culture